ALAT DAUR ULANG BOTOL PET MENJADI BAHAN BAKU FILAMEN UNTUK 3D PRINTER - Bambang Supriyanto; Deni Andriyansyah (Teknika, 2025)
Plastic bottles made from Polycarbonate (PC) are widely used for mineral water packaging. The use of these materials results in a large amount of plastic-type waste, which is bad for the environment if not handled properly. The plastic bottle packaging is only recommended for one-time use. Plastic bottles made from PET can be processed and used as raw material for 3D printers. The processing of these plastic bottles uses microcontroller technology, which is made to adjust the temperature for heating the PET bottle material, as well as to control the rotation of the servo motor used to push and pull the rolling material. The control method used uses the PID theorem, which is regulated manually by trial and error, where this research only tests how much temperature is needed and the motor pull speed (RPM) to produce raw materials for 3D printers. The expected diameter of the process results has been determined with the size of the nozzle diameter used, which is 1.7 mm. From the test results after the tool was made, plastic bottles that had been cut like ribbons with a width of 1 mm, a heating treatment of 170°C with a tensile speed by adjusting the speed of 20.8% and 40.8% got the best results visually, smooth, clear and bonding is pretty good.